Urban water and nutrient flows in Kumasi, Ghana - Erni, M.; Bader, H.P.; Drechsel, Pay; Scheidegger, R.; Zurbrugg, C.; Kipfer, R. (Informa UK Limited, 2011)
Material flow analysis was applied to model different scenarios which help better identify and quantify water supply and wastewater pollution problems in the city of Kumasi, Ghana. Results show that despite a relative abundance of water resources in the surrounding area of the city, drinking water consumption will remain at a low level (from 49 + 4 l/cap/day in 2006 to 59 + 5 l/cap/day in 2015). Changing sanitation practices to using more flush toilets will require significantly more water if these toilets are to be used adequately. The water-nutrient balance shows that total nitrogen (N) and phosphorus (P) outputs of the modelled area are 10 times higher than system inputs, most of this being attributed to human wastes from sanitation. A number of possible measures to reduce nutrient flows into water bodies were identified and quantified, showing the usefulness of the applied model in providing estimates for municipal decision-makers.